Analisis Modal Kerja Dalam Meningkatkan Profitabilitas Pada PT. Kereta Api Indonesia DIVRE I Sumut - Ikhsan Abdullah (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2020)
This study aims to determine and analyze how the net working capital at PT. Kereta Api Indonesia DIVRE I Sumut Tbk, in increasing profitability at PT. Kereta Api Indonesia DIVRE I Sumut Tbk, This research was conducted using a descriptive research method with the variables used are working capital using net working capital and profitability using Return on Investment (ROI) and Return on Equity (ROE). This research was conducted at PT. Kereta Api Indonesia DIVRE I Sumut Tbk using quantitative data types and research data sources, namely secondary data in the form of financial statements of PT. Kereta Api Indonesia DIVRE I North Sumatra Tbk. While the data collection techniques through documentation. Based on the research results net working capital of PT. Kereta Api Indonesia DIVRE I Sumut Tbk experienced a decrease due to the increase in current assets not proportional to the increase in current liabilities in the form of trade payables, bank loans and other financial institutions, advances from employers, unearned income, accrued expenses, bonds payable, debt retention , sukuk payables and other short-term liabilities while the factor is because long-term debt has matured so that it becomes short-term debt. This is the cause of disruption to the profitability of PT. Kereta Api Indonesia DIVRE I Sumut Tbk, namely the decline in profit after tax due to cost of revenue, joint venture profits, operating expenses, finance expenses, and income tax expenses increased, while the fact was that interest on bank loans and income taxes increased drastically